Modification of the Indonesian Academic Cyberloafing Scale (IACS): A tool for assessing online deviance in educational contexts - Fuadi, Muhammad Nurrifqi; Pradana, Rizal Galih; Budiman, Mutmainnah; Fauziyah, Farah; Medina, Karima Nada; Ramadhan, Syukron; Helmi, Avin Fadilla; Widhiarso, Wahyu (Humanitas: Indonesian Psychological Journal, 2025)
The initial ease of internet use has led to new challenges, one of which is the phenomenon of cyberloafing. Cyberloafing refers to the activity of accessing the internet during learning processes. The aim of this study is to modify the cyberloafing scale within an educational setting in Indonesia using the dimensions of sharing, shopping, real-time updating, accessing online content, and gaming/gambling. The modifications include contextualizing the original and adding new relevant items. Data collection was conducted using purposive sampling, involving 235 university students from various higher education institutions in Indonesia. The method used to test the validity of the cyberloafing model was confirmatory factor analysis. The results showed that out of 65 items, 20 were found to be valid, with a satisfactory total Cronbach’s alpha of 0.73-0.93 and McDonald’s omega of 0.71-0.93 for measuring reliability for each dimension of cyberloafing. The practical implication of this measurement tool is that it can be used to assess the intensity of cyberloafing among higher education students in Indonesia